[Benito Teehankee was selected for inclusion in the Baron's Who's Who of the Asian Pacific Rim] - Teehankee, Benito L. (Animo Repository, 1997)
Benito Teehankee, School Director of DLSU-College of St. Benilde's Information Technology and faculty member of the Behavioral Sciences Department, was selected for inclusion in the upcoming edition of Baron's Who's Who of the Asian Pacific Rim.